Combined Hub Location and Service Network Design Problem: A Case Study for an Intermodal Rail Operator and Structural Analysis. Issue 1 (January 2023) - Elbert, Ralf; Rentschler, Johannes; Schwarz, Jessica
In intermodal transportation, hubs are facilities that perform switching, sorting, connecting, and consolidating functions between many origins and destinations. Hub location problems (HLP) accordingly involve the location of hubs but include abstract network design decisions as well. In the past, the strategic location decision and the more tactical network design decision, in the form of a service network design problem (SNDP), have been considered separately. However, the SNDP is based on an existing hub network and the HLP could benefit from a more detailed network design. For this reason, this paper presents the combined hub location and service network design problem (C-HL-SNDP), which considers the strategic and tactical planning dimensions in an integrated manner. In a case study of a German intermodal operator, the paper shows that integrated modeling can be used to produce very good and realistic solutions that generate added value. The combined model with a classical HLP approach is compared and a structural analysis of the solution properties is performed. With this, it can be shown that the different consideration of economies of scale and economies of density lead to fundamentally different solutions.